Zinc Content, Suppleness and Favorability Test on Anchovy Flour Fortified Cob Meatballs - Ruli Bahyu Antika; Septy Handayan; Wahyu Ningtyias, Farida; Yunita Satya Pratiwi; Septi Nur Rachmawati; Abdul Azis Akbar; Lirista Dyah Ayu Oktafiani (Universitas Nahdlatul Ulama Surabaya, 2023)
Stunting in Jember Regency is the eighth most common condition in East Java, affecting up to 30% of the 180,000 children under the age of five. The creation of meatballs made from tuna fortified anchovy, which are increasingly rich in nutrients like zinc, will help to overcome nutritional issues. The aim of this research was to look at zinc levels, elasticity, and organoleptic properties. The aim of this study was to look at the zinc levels, elasticity, and organoleptic consistency of tuna fish balls after fortification with anchovy flour and chewers, which could help stunted toddlers improve their nutritional status. This is a true experimental study with a pre and post control group configuration. The sample size was set at 27 (eight samples from the treatment group and one sample from the control group). Zinc levels, elasticity, and organoleptic consistency are all measured in the lab through observation. On zinc levels, ANOVA Two Way was used to analyze data presentation. Zinc levels of 0.001 mg/100 gr and elasticity of 707.38 4.13 gf were found in tuna fish balls until they were reinforced with anchovy flour and chewers. The interaction of zinc content, elasticity, and organoleptic quality of anchovy meal fortification (0, 18%, and 35%) and thickener (carrageenan and STTP) has a major effect on zinc content, elasticity, and organoleptic quality (physical and preferences include taste, aroma, color and texture). The best tuna meatballs in terms of general nutritional content and chewiness are tuna fish balls fortified by 35% anchovy and with carrageenan as thickener. His general favorite is tuna fish balls which are not fortified with anchovy flour and without chewing. Future research is expected to find alternatives to other highly nutritious fish with good acceptance